2021
DOI: 10.2196/23806
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-Based Activity Trackers as a Tool for Physical Activity Monitoring in Epidemiological Studies During the COVID-19 Pandemic: Development and Usability Study

Abstract: Background Consumer-based physical activity trackers have increased in popularity. The widespread use of these devices and the long-term nature of the recorded data provides a valuable source of physical activity data for epidemiological research. The challenges include the large heterogeneity between activity tracker models in terms of available data types, the accuracy of recorded data, and how this data can be shared between different providers and third-party systems. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…Although there is evidence supporting interdevice validity and reliability between different types of wearable activity trackers [31], the method for measuring physical activity should be standardized. Henriksen et al [32] developed a system to record data on physical activity from different types of wearable activity trackers (Apple, Fitbit, Garmin, Oura, Polar, Samsung, and Withings) and confirmed that there was a significant reduction in the daily step count and energy expenditure during the lockdown period. However, the development of a more accurate and more reliable device is a challenge for the future.…”
Section: Physical Activity During the Covid-19 Pandemicmentioning
confidence: 99%
“…Although there is evidence supporting interdevice validity and reliability between different types of wearable activity trackers [31], the method for measuring physical activity should be standardized. Henriksen et al [32] developed a system to record data on physical activity from different types of wearable activity trackers (Apple, Fitbit, Garmin, Oura, Polar, Samsung, and Withings) and confirmed that there was a significant reduction in the daily step count and energy expenditure during the lockdown period. However, the development of a more accurate and more reliable device is a challenge for the future.…”
Section: Physical Activity During the Covid-19 Pandemicmentioning
confidence: 99%
“…From the evidence included, we found a significant increase in the use of wearables to improve physical activity during the confinement or lockdown periods [21,24]. There is a convincing evidence to show that there is a significant decrease in physical activity and increased sedentary time in people around the world when judged objectively using wearables [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Figure 2 represents the summary of our findings.…”
Section: Discussionmentioning
confidence: 69%
“…Seven studies administered smartphone-based physical activity measurement through inbuilt accelerometers from which the captured data were transferred to the cloud server and visualized in smartphone applications [16-19, 21, 24, 31]. Majority of studies (n = 9; 53%) employed wrist bands and wristwatches of multiple technology firms (Apple, Samsung, Xiaomi) and wearable research-based accelerometers [20,23,25,26,[28][29][30]32]. A few studies (n = 4; 24%) reported the psychometrics of the wearables, and lowto-moderate validity was found [21,22,27].…”
Section: Wearables and The Measurement Of Physical And Physiological Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…For these providers, the communication is performed by the provider’s mobile application and uploaded to the mSpider server back-end via the mSpider mobile application. One of the applications performed was the identification of changes in physical activity levels during COVID-19 (coronavirus disease 2019 pandemic), showing that the mSpider system can be a valuable tool for collection of long-term data on physical activity, including historical data and detecting changes in physical activity over time [ 26 ].…”
Section: Practical Use Of Activity Trackers In Clinical Researchmentioning
confidence: 99%